Bioecology of rust on Dendranthema grandiflora in Yogyakarta-Indonesia - Tri Martini; Bambang Hadi Sutrisno; Suhardi Suhardi; Prapto Yudono; Sudarmaji Sudarmaji (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2022)
Rust leaf disease is the main disease on chrysanthemum (Dendranthema grandiflora) plantations in the district of Sleman, Yogyakarta Special Region. In 2006, the symptoms of leaf rust were initially found in chrysanthemum farms in village of Hargobinangun and surrounding areas. Since then it has been consistently spreading to other areas throughout Yogyakarta-Indonesia. Puccinia horiana is closely associated with rust leaf disease. This research was aimed to investigate the distribution, incidence, and severity of chrysanthemum rust disease in chrysanthemum plantations in Yogyakarta. The survey was conducted based on a randomized stratified approach. The entire district was divided into five observation sites, with each location consisting of three to four chrysanthemum farm sites owned by farmers. The results showed that rust leaf disease was distributed in all sites. The average of disease incidence found in the observation sites was 97.13%, meanwhile the average of disease severity was 55.19%. The highest disease incidence was found in Kaliurang 98.44%, followed by Wonokerso of 98.33%, Gondanglegi of 96.87%, Boyong of 96.25%, and Sidorejo of 95.83%. The highest disease severity was found in Wonokerso 58.75%, followed by Gondanglegi 56.92%, Kaliurang 53.39%, Sidorejo 54.89%, and Boyong 52.01%. The lower plant cultivation site, the lower incidence of rust disease.